Pembelahan Politik Kiai NU di Pilgub Jatim 2018 - Rohim, Ainur; Mahardika, Mayuko Galuh (Jurnal Transformative, 2018)
The realm of East Java politics which has been known as the main community of Traditional Islam, bequeaths a separate record of the dynamics and political maneuvers of NU strategic elites (Kiai) in the context of 2018 East Java Pilgub. Similar political realities have occurred since the East Java Pilgub in 2008 and 2013 . One thing that is most useful and more in several perspectives is the change in political division among the NU East Java kiai in the 2018 Pilgub. Things that happened also in the East Java Pilgub 2008 and 2013 ago. The writing of this journal is preceded by the existence of research with qualitative methods with primary data collection through interviews with people who understand this case study and also supported by secondary data. The author will analyze the phenomena that occur with the cleavage theory described by Peter Mair (2014).